Exploration of Interaction and Mapping Interaction Research in Second Language Learning Content Analysis Based on Books Rod Ellis - Ahmad Fadhel Syakir Hidayat; Mamluatul Hasanah; Abdul Latif; Slamet Mulyani; Rifqi Aulia Rahman; Azwar Annas; Akhirudin (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2024)
This study examines the concepts of Interaction and Mapping Interaction Research in Second Language Learning in the Classroom: Content Analysis Based on Rod Ellis's "Language Teaching Research and Language Pedagogy." The study applies a qualitative approach with a literature review design, utilizing data collection techniques such as documentation and literature review, followed by content analysis. This study indicates that Rod Ellis discusses the abilities involved in interaction, employing a sociocultural theory perspective to examine the development of second language learning. This theory emphasizes microgenetic and quasi-experimental studies on language learning through social interaction and internal learner growth. Rod Ellis also studies how classroom input and interaction improve second language learning using interactionist-cognitive theory, which emphasizes the function of interaction in delivering input that learners inwardly analyze. This perspective draws upon research employing descriptive/exploratory approaches.